THE IMPACT OF DEMAND SIDE MANAGEMENT ON THE UTILIYU ACTIONS FOR IMPROVING THE OPERATION OF DISTRIBUTION SYSTEMS CONSISTING PV GENERATOR - Hanhan, Malaka (An-najah national university, 2025)
This thesis investigates the impact of demand-side management (DSM) strategies on utility actions for improving the operation of distribution systems with high photovoltaic (PV) penetration. A case study was conducted using OpenDSS software, applying the IEEE 30-bus test network. A 50 MW PV system was integrated into bus 21, demonstrating its ability to reduce total electrical losses in transmission lines from 9308.34 kW to 7742.83 kW. Meanwhile, the study examined the application of various DSM strategies to further enhance network performance after hosting the PV system. Direct Load Control (DLC) reduced network losses to 5365.5 kW, while the Time-of-Use (TOU) tariff strategy significantly reduced losses to 3736.9 kW. Additionally, the Conservation Voltage Reduction (CVR) strategy improved overall network voltage profiles, particularly decreasing the voltage at bus 21 from 1.0524 p.u. to 1.0442 p.u. and at bus 11 from 1.0819 p.u. to 1.0748 p.u. The hosting capacity analysis revealed that increasing PV penetration initially reduced electrical losses, with significant reductions observed at penetration levels of 15 MW, 30 MW, 50 MW, and 70 MW, corresponding to losses of approximately 9830 kW, 8000 kW, 7000 kW, and 5800 kW, respectively. However, beyond a hosting capacity of 70 MW, further increases in PV penetration led to a rise in losses, reaching 7900 kW at 150 MW and exceeding 12,200 kW at 200 MW. The use of DSM strategies effectively mitigated these losses even at higher penetration levels. For instance, DLC reduced losses to approximately 6000 kW, and TOU reduced them further to 5000 kW at a 200 MW PV hosting capacity. These findings highlight the critical role of DSM strategies in enhancing the operational efficiency and reliability of distribution systems with high PV integration
تأثير إدارة الطلب على الاجراءات المطبقة من قبل الشركات الكهربائية والتي تستخدم لتحسين شبكات التوزيع التي تتضمن الانظمة الكهروضوئية